Research handbook on EU data protection law - Kosta, Eleni 1979-; Leenes, Ronald 1964-; Kamara, Irene (Edward Elgar Publishing, 2022)
"Bringing together leading European scholars, this thought-provoking Research Handbook provides a state-of-the-art overview of the scope of research and current thinking in the area of European data protection. Offering critical insights on prominent strands of research, it examines key challenges and potential solutions in the field. Chapters explore the fundamental right to personal data protection, government-to-business data sharing, data protection as performance-based regulation, privacy and marketing in data-driven business models, data protection and judicial automation, and the role of consent in an algorithmic society.
Keywords: Data protection / Law and legislation / European Union countries; European Parliament / General Data Protection Regulation; Privacy, Right of / European Union countries; Consent (Law) / European Union countries; Consent (Law); Data protection / Law and legislation; Privacy, Right of; European Union countries